Research on the Influencing Factors of Diversification of Innovation Sources. Issue 4 (March 2019) - Wei, Tie; Yang, Mei; Gong, Yingge; Xie, Linling
Abstract: In this paper, we explore the influencing factors of the decentralization of innovation sources from the overall social level. More specifically, the work intends to examine how the social environment (intellectual property judicial protection, Internet, knowledge environment, Salary Income), technical characteristics (technical opportunities, industrial agglomeration, technology spillovers, absorptive capacity, technological preference) and innovation rent (transfer of technology, commercialization) affect the decentralization of innovation sources through patent data. Results show that the effect of Salary Income, technological opportunities, technological absorptive capacity and innovation rent on the decentralization of the overall source of innovation are significant.